12x=(x+3)(x+3)

Simple and best practice solution for 12x=(x+3)(x+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12x=(x+3)(x+3) equation:



12x=(x+3)(x+3)
We move all terms to the left:
12x-((x+3)(x+3))=0
We multiply parentheses ..
-((+x^2+3x+3x+9))+12x=0
We calculate terms in parentheses: -((+x^2+3x+3x+9)), so:
(+x^2+3x+3x+9)
We get rid of parentheses
x^2+3x+3x+9
We add all the numbers together, and all the variables
x^2+6x+9
Back to the equation:
-(x^2+6x+9)
We add all the numbers together, and all the variables
12x-(x^2+6x+9)=0
We get rid of parentheses
-x^2+12x-6x-9=0
We add all the numbers together, and all the variables
-1x^2+6x-9=0
a = -1; b = 6; c = -9;
Δ = b2-4ac
Δ = 62-4·(-1)·(-9)
Δ = 0
Delta is equal to zero, so there is only one solution to the equation
Stosujemy wzór:
$x=\frac{-b}{2a}=\frac{-6}{-2}=+3$

See similar equations:

| 17x=-185 | | 6=12-2f | | 3a-4/2-2a+5/4+3/2=0 | | 40=n*5 | | 6=12–2f | | -2(x+)=2(x-1) | | 31x-12=30 | | 12x=(x+2)(x+2) | | 4/5(5p–20)+6=10 | | 74=3x+20 | | -4b+7=35 | | 4x2=-6 | | 8x+6x^2=-5x+3x^2 | | .75x=225-x | | 41.8c=133.76 | | C(x)=25x+360 | | 3x2+5x+6+x−1x+2=7x+3x | | 7(x1)=49 | | 13u–3u=10 | | 3(n+3)=24 | | 4x+2x-5=-1 | | 18+1/3k=-8 | | 8x-16=3x | | 6x/4-5=1 | | (3a-4/2)-(2a+5/4)+(3/2)=0 | | 3x+15=3x-17 | | 34=4c-6 | | 54s+36=24s+3 | | C=4.5+0.5m | | 7+17y=58 | | -1(1x-5=9 | | 6(n+3)=24 |

Equations solver categories